Safety of Parecoxib in Asthmatic Patients with Aspirin-Exacerbated Respiratory Disease (2011)
BACKGROUND Aspirin-exacerbated respiratory disease (AERD) affects a subset of patients with asthma. Cyclooxygenase 2 inhibitors are a safe alternative in patients with AERD. Parecoxib is the first cyclooxygenase 2 selective drug for parenteral administration, especially useful after surgery thanks to its analgesic power. The aim of the study is to assess the tolerance of parecoxib (Dynastat; Pfizer) given by intramuscular route in patients with AERD. METHODS Patients evaluated were referred to the Pneumology and Respiratory Allergy Department of the Hospital Clinic (Barcelona, Spain) for asthma exacerbations precipitated by 2 or more different non-steroidal anti-inflammatory drugs (NSAIDs). AERD was confirmed by a nasal challenge test with aspirin. Patients were challenged with parecoxib, and urine samples were collected to measure the leukotriene E(4) concentration. RESULTS Ten patients were challenged with parecoxib. No symptoms were reported with any of the administered doses, and there were no signs of immediate or delayed hypersensitivity. There were no alterations in the forced expiratory volume in 1 s or in acoustic rhinometry measurements. No significant differences between leukotriene E(4) levels were detected. CONCLUSION The drug was well tolerated by all patients, with no adverse reactions. This lack of reactions found in our study supports the fact that parecoxib could be a safe alternative in postsurgery analgesia in NSAID-intolerant asthma patients.